Dose-dependent effects of morphine on lipopolysaccharide (LPS)-induced inflammation, and involvement of multixenobiotic resistance (MXR) transporters in LPS efflux in teleost fish. (February 2017) - Mottaz, Hélène; Schönenberger, Rene; Fischer, Stephan; Eggen, Rik I.L.; Schirmer, Kristin; Groh, Ksenia J.
Abstract: Opioid drugs, such as morphine (MO), detected in aquatic environments worldwide, may harm fish due to their semi-persistence and ability to potently interact with molecular targets conserved across vertebrates. Here, we established a waterborne bacterial lipopolysaccharide (LPS) challenge assay with zebrafish embryos as a model to investigate chemically-induced disruption of the innate immune system, and used it to study the effects of MO exposure. Exposure to 1 mg/L MO resulted in pronounced immunosuppression, reflected in downregulation of several inflammation-related genes, including myd88, trif, traf6, p38, nfκb2, il-1β, il-8 and ccl34a . Fish exposed to 1 mg/L MO accumulated 11.7 ng/g (wet weight) of MO, a concentration comparable to that reported in blood of chronic drug abusers subject to higher infection rates. Surprisingly, exposure to lower MO concentrations (100 ng/L–100 μg/L) led to exacerbation of LPS-induced inflammation. Two ATP-binding cassette (ABC) transporters known to be involved in the xenobiotic efflux - abcb4 and abcc2, also known as multixenobiotic resistance (MXR) transporters - were downregulated at 100 ng/L MO. We hypothesized that ABC/MXR transporters could modulate the severity of inflammation by being involved in efflux of LPS, thus regulating its accumulation in the organism. Indeed, we could demonstrate that blocking of ABC/MXR transporters by an inhibitor, cyclosporine A, results in stronger inflammation, coinciding with higher LPS accumulation, as visualized with fluorescently labeled LPS. Our work demonstrates that MO can disrupt fish innate immune responses at environmentally relevant concentrations. We also provide evidence for a role of ABC/MXR transporters in LPS efflux in fish. These finding may be applicable across other taxa, as ABC transporters are evolutionary conserved. Since diverse environmentally present chemicals are known to interfere with ABC/MXR transporters' expression or activity, our discovery raises concerns about potential adverse effects of such compounds on the immune system responses in aquatic organisms. Graphical abstract: Highlights: Waterborne LPS challenge optimized to study chemical effects on inflammation in fish. Morphine disrupted immune responses at environmentally relevant concentrations. Stronger and weaker inflammation observed at low and high morphine, respectively. ABC/MXR transporters shown to play a role in LPS efflux; some suppressed by morphine. Pollutants interfering with ABC transporters may cause immune system disruption. Abstract : We show that ABC/MXR transporters may play a role in lipopolysaccharide detoxification in fish; pollutants affecting ABC/MXR transporters' activity may cause immune system disruption.